Artificial Intelligence and Symbolic Computation 13th International Conference, AISC 2018, Suzhou, China, September 16-19, 2018, Proceedings - Fleuriot, Jacques; Wang, Dongming; Calmet, Jacques; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book constitutes the refereed proceedings of the 13th International Conference on Artificial Intelligence and Symbolic Computation, AISC 2018, held in Suzhou, China, in September 2018. The 13 full papers presented together with 5 short and 2 invited papers were carefully reviewed and selected from 31 submissions. The AISC conference is an important forum when it comes to ensuring that ideas, theoretical insights, methods and results from traditional AI can be discussed and showcased, while fostering new links with other areas of AI such as probabilistic reasoning and deep learning. .
Artificial Intelligence, Theorem Proving and SAT Solving -- Symbolic and Numerical Computation -- Intelligent Documents and Collective Intelligence.
Keywords: Artificial intelligence; Computer science -- Mathematics; Machine theory; Application software; Artificial Intelligence; Mathematical Applications in Computer Science; Formal Languages and Automata Theory; Computer and Information Systems Applications